Financial Digitalization for SMEs through the SIAPIK Application - Fisla Wirda; H Herizon; Y Yulherniwati (CV. Media Digital Publikasi Indonesia, 2024)
Good financial reporting is needed so that financial reports are available accurately and on time. Azizah's crackers business is an SME located in Batu Gadang Village, Lubuk Kilangan District, Padang City West Sumatra Province. One of the problems in this business is that financial recording is still done manually, so it requires a long process and a high error rate and it is difficult to know the cash flow position quickly and accurately. Making good financial reports requires time as well as knowledge and expertise in the field of accounting, but not all business people have good knowledge and skills in this field. For this reason, an application is needed that helps create financial reports. In this community service activity, the SIAPIK Application (Financial Information Reporting Application System) because this application is issued by Bank Indonesia which has the standards of the Indonesian Accounting Association, is free, and can be used for all types of businesses including manufacturing. Method of implementing activities: planning and preparation through surveys or initial interviews with cracker Uzziah leaders to understand needs and problems, Implementation by providing training and assistance in using SIAPIK, Evaluation is carried out by assessing participants abilities in running the SIAPIK application, Monitoring and follow-up assistance by scheduling periodic visits, Reporting by making activity reports. Azizah's crackers employees participated in the training well and smoothly, the SIAPIK application has been installed on their smartphones, and employees can input data, make transactions, and issue business financial reports